Preparation method of aluminum-iron co-doped V6O13 electrode material and application of aluminum-iron co-doped V6O13 electrode material in aqueous zinc ion battery

Through the preparation and application of aluminum-iron-iron co-doped V6O13 electrode material, the problem of insufficient performance of existing aqueous zinc-ion battery electrode materials has been solved, and the conductivity and rate performance has been improved, with the advantages of low cost, environmental protection and high safety.

CN119542401AInactive Publication Date: 2025-02-28LIAONING UNIVERSITY
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411777961.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-02-28
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing aqueous zinc ion battery electrode materials, such as manganese oxides and Prussian blue compounds, have problems such as poor conductivity, poor rate performance and limited cycle performance, which are difficult to meet the growing demand.

Method used

The preparation method of aluminum-ferrous aluminum-doped V6O13 electrode material is used to prepare Al/Fe-V6O13 electrode material through hydrothermal reaction and calcination process, and is used in aqueous zinc ion batteries.

Benefits of technology

It significantly improves the conductivity of the material and the ion diffusion rate, reduces internal resistance, improves specific capacity and rate performance, has the characteristics of low cost, environmentally friendly, and high safety, and improves energy density and power density.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of materials, and particularly relates to a preparation method of an aluminum-iron co-doped V6O13 electrode material and application of the aluminum-iron co-doped V6O13 electrode material in an aqueous zinc ion battery. Al / Fe-V6O13 is prepared through a simple solvothermal method, metal aluminum and iron ions are co-doped in the electrode material through reaction, and aluminum and iron ions are co-doped in V6O13, so that active sites of the electrode material are increased, ion diffusion and charge transfer are effectively promoted, the conductivity of Al / Fe-V6O13 is improved, the internal resistance of Al / Fe-V6O13 is reduced, and the performance of the electrode material is improved. And the structural flexibility and stability of the material are maintained, so that the overall performance of the water-based zinc ion battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of material technology and specifically relates to an aluminum-iron co-doped V6O 13 The invention relates to a method for preparing electrode materials and their application in aqueous zinc ion batteries. Background Art

[0002] In recent years, with the growing demand for mobile power, the conflict between excessive energy consumption and environmental protection has gradually intensified. There is an urgent need to find environmentally friendly, sustainable and efficient energy storage technologies. The emergence of lithium-ion batteries has improved the energy availability of mobile power devices. Unfortunately, the unreliability of lithium-ion batteries and the scarcity of lithium materials make them difficult to apply on a large scale, which seriously hinders their development and application in the field of large-scale energy storage. The development of energy storage devices is an important way to solve the energy crisis and utilize efficient renewable energy. Therefore, researching and developing new energy storage battery systems that can replace lithium-ion batteries and have the characteristics of low cost, high energy, high safety and green environmental protection is an important direction for sustainable development.

[0003] Aqueous zinc-ion batteries, unlike traditional alkaline zinc-manganese batteries and nickel-zinc batteries, use neutral or weakly acidic zinc salt aqueous solutions as electrolytes (pH: 3.6-6.0), have low requirements for packaging conditions, low production costs, are safe and environmentally friendly, and have good development prospects in the field of large-scale energy storage. They are regarded by researchers as a more promising battery research direction. In particular, compared with organic electrolytes, aqueous electrolytes have the advantages of high ionic conductivity, high safety, low cost, and easy packaging, thereby achieving better rate performance. However, the electrode materials currently used, such as manganese oxides and Prussian blue compounds, have unnecessary phase changes, inevitable dissolution, and unsatisfactory reversibility, resulting in poor conductivity, poor rate performance, and limited cycle performance, which are difficult to meet the growing demand. Summary of the invention

[0004] In order to solve the above problems, the present invention provides an aluminum-iron co-doped V6O 13 The invention relates to a method for preparing electrode materials and their application in aqueous zinc ion batteries.

[0005] The technical solution adopted by the present invention is:

[0006] Aluminum-iron co-doped V6O 13 The electrode material and the preparation method thereof comprise the following steps:

[0007] Vanadium pentoxide, aluminum nitrate and ferric nitrate were weighed and dissolved in deionized water and anhydrous ethanol, mixed and stirred at room temperature to fully mix, and the fully mixed solution was transferred to a stainless steel hydrothermal reactor lined with polytetrafluoroethylene for hydrothermal reaction, cooled to room temperature, centrifuged to remove residual reactants, freeze-dried, and then the product was placed in a tubular furnace under a nitrogen environment for calcination to obtain Al / Fe-V6O 13 Electrode material.

[0008] Preferably, the above-mentioned Al / Fe-V6O 13 The preparation method of the electrode material is as follows: in molar ratio, vanadium pentoxide: aluminum nitrate: iron nitrate = 2.2: 0.08-0.13: 0.07-0.12.

[0009] Preferably, the above-mentioned Al / Fe-V6O 13 The invention relates to a method for preparing an electrode material. The aluminum nitrate and the iron nitrate are Al(NO3)3·9H2O and Fe(NO3)3·9H2O.

[0010] Preferably, the above-mentioned Al / Fe-V6O 13 The preparation method of the electrode material comprises the following conditions: the hydrothermal reaction is carried out at 160° C. for 24 hours.

[0011] Preferably, the above-mentioned Al / Fe-V6O 13 The preparation method of the electrode material comprises the following steps: calcining at 350°C for 1 hour.

[0012] Any of the above Al / Fe-V6O 13 Application of electrode materials in aqueous zinc-ion batteries.

[0013] Furthermore, the above application method comprises the following steps:

[0014] 1) Preparation of positive electrode: Al / Fe-V6O 13 After the material is mixed evenly with the binder and the conductive material, a small amount of NMP is added as a solvent. After mixing evenly, it is directly applied on the substrate carbon paper, dried in a vacuum drying oven, and taken out to obtain a coating of Al / Fe-V6O 13 Positive electrode of the material;

[0015] 2) Preparation of negative electrode: Grind the zinc sheet with sandpaper to remove the oxide layer on the surface, and cut the polished zinc sheet into a circular negative electrode sheet with a diameter of 12 mm;

[0016] 3) The positive electrode sheet prepared in step 1) is used as the positive electrode, the negative electrode sheet prepared in step 2) is used as the negative electrode, and the electrolyte is 3M zinc trifluoromethanesulfonate to obtain an aqueous zinc ion battery.

[0017] Furthermore, in the above application, in step 1), the binder is PVDF.

[0018] Furthermore, in the above application, in step 1), the conductive material is Super-p.

[0019] Furthermore, in the above application, in step 2), the zinc sheet has a thickness of 0.1 mm to 0.2 mm and a purity of 99% to 99.99%.

[0020] The beneficial effects of the present invention are:

[0021] 1. By introducing aluminum and iron ions during the synthesis process, the conductivity and ion diffusion rate of the material are significantly improved, and the internal resistance is reduced.

[0022] 2. The introduction of aluminum and iron ions increases its active sites, thereby improving the specific capacity and rate performance of the material during the charge and discharge process.

[0023] 3. It has the characteristics of low cost, environmental friendliness and high safety.

[0024] 4. It has the advantages of higher energy density and power density.

[0025] 5. The synthesis process and assembly process are simple, easy to operate and control, and suitable for continuous large-scale production.

[0026] 6. After modification, the capacity of the electrode material increased from 496 mAh / g to 590 mAh / g.

[0027] 7. The method of the present invention is also applicable to other metal oxide positive electrode materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 V6O prepared in Example 1 13 and Al / Fe-V6O 13 XRD spectrum of .

[0029] Figure 2 V6O prepared in Example 1 13 and Al / Fe-V6O 13 GCD spectrum.

[0030] Figure 3 V6O prepared in Example 1 13 and Al / Fe-V6O 13 Cyclic voltammetry curve of .

[0031] Figure 4 V6O prepared in Example 1 13 and Al / Fe-V6O 13 Specific capacity diagram. DETAILED DESCRIPTION

[0032] The technical solution of the present invention is further described below, but is not limited thereto. Any modification or equivalent replacement of the technical solution of the present invention without departing from the spirit and scope of the technical solution of the present invention should be included in the protection scope of the present invention.

[0033] Example 1 Aluminum-iron co-doped V6O 13 Preparation

[0034] (I) Al / Fe-V6O 13 The preparation method is as follows:

[0035] 0.4 g of vanadium pentoxide, 0.04 g of aluminum nitrate nonahydrate and 0.04 g of ferric nitrate nonahydrate were weighed and dissolved in 20 mL of deionized water and 25 mL of anhydrous ethanol. After mixing, they were stirred at room temperature to be fully mixed. The fully mixed solution was transferred to a stainless steel hydrothermal reactor lined with polytetrafluoroethylene, and the hydrothermal reaction was carried out at 160 ° C for 24 h. When the reactor was completely cooled to room temperature, the product was taken out, washed three times by centrifugation with deionized water and anhydrous ethanol respectively, freeze-dried for 24 h, and then the product was placed in a tubular furnace under a nitrogen environment for calcination. The calcination condition was 350 ° C for 1 h to obtain Al / Fe-V6O 13 Electrode material.

[0036] (II) Testing

[0037] Figure 1 It is V6O 13 and Al / Fe-V6O prepared in this embodiment 13 XRD spectrum of Figure 1 It can be seen that after aluminum and iron co-doping, the XRD spectrum of the sample did not show obvious changes. The shift of individual peaks and the decrease in crystallinity indicate that aluminum and iron ions were successfully doped into V6O 13 middle. Figure 2 It is V6O 13 and Al / Fe-V6O 13 GCD spectrum of . Figure 2 It can be seen that the performance of the electrode material is significantly improved after doping. Figure 3 It is V6O 13 and Al / Fe-V6O 13 Cyclic voltammetry curve of Figure 3 It can be seen that Al / Fe-V6O 13 The area enclosed is significantly larger than that of pure V6O 13 , which indicates that Al / Fe-V6O 13 The capacity is greater than pure V6O 13 . Figure 4 It is V6O13 and Al / Fe-V6O 13 Specific capacity diagram. Figure 4 It can be seen that Al / Fe-V6O 13 The specific capacity is much higher than that of pure V6O 13 .

[0038] Example 2 Aluminum-iron co-doped V6O 13 Preparation

[0039] 0.4 g of vanadium pentoxide, 0.03 g of aluminum nitrate nonahydrate and 0.03 g of ferric nitrate nonahydrate were weighed and dissolved in 20 mL of deionized water and 25 mL of anhydrous ethanol. After mixing, they were stirred at room temperature to be fully mixed. The fully mixed solution was transferred to a stainless steel hydrothermal reactor lined with polytetrafluoroethylene, and the hydrothermal reaction was carried out at 160 ° C for 24 h. When the reactor was completely cooled to room temperature, the product was taken out, washed three times by centrifugation with deionized water and anhydrous ethanol respectively, freeze-dried for 24 h, and then the product was placed in a tubular furnace under a nitrogen environment for calcination. The calcination condition was 350 ° C for 1 h to obtain Al / Fe-V6O 13 Electrode material.

[0040] Example 3 Aluminum-iron co-doped V6O 13 Preparation

[0041] 0.4 g of vanadium pentoxide, 0.05 g of aluminum nitrate nonahydrate and 0.05 g of ferric nitrate nonahydrate were weighed and dissolved in 20 mL of deionized water and 25 mL of anhydrous ethanol. The mixture was stirred at room temperature to make it fully mixed. The fully mixed solution was transferred to a stainless steel hydrothermal reactor lined with polytetrafluoroethylene, and the hydrothermal reaction was carried out at 160 ° C for 24 h. When the reactor was completely cooled to room temperature, the product was taken out, washed three times by centrifugation with deionized water and anhydrous ethanol respectively, freeze-dried for 24 h, and then the product was placed in a tubular furnace under a nitrogen environment for calcination. The calcination condition was 350 ° C for 1 h to obtain Al / Fe-V6O 13 Electrode material.

[0042] Example 4 Preparation of negative electrode material

[0043] A zinc sheet with a thickness of 0.1 mm and a purity of 99.99% was repeatedly polished with sandpaper to remove the oxide layer on the surface, and the polished zinc sheet was cut into a circular negative electrode sheet with a diameter of 12 mm for later use.

[0044] Example 5 Preparation of negative electrode material

[0045] A zinc sheet with a thickness of 0.2 mm and a purity of 99.99% was repeatedly polished with sandpaper to remove the oxide layer on the surface, and the polished zinc sheet was cut into a circular negative electrode sheet with a diameter of 12 mm for later use.

[0046] Example 6 Preparation of aqueous zinc ion battery

[0047] 1) Preparation of positive electrode: The aluminum-iron prepared in Example 1 was co-doped with V6O 13 After the electrode material is evenly mixed with PVDF and Super-p, a small amount of NMP is added as a solvent. After being evenly mixed, it is directly applied on the substrate carbon paper, dried in a vacuum drying oven, and taken out to obtain a coating with aluminum-iron co-doped V6O 13 The positive electrode;

[0048] 2) The positive electrode sheet prepared in step 1) was used as the positive electrode, the negative electrode sheet prepared in Example 4 was used as the negative electrode, and 3M zinc trifluoromethanesulfonate was selected as the electrolyte to obtain an aqueous zinc ion battery and perform electrochemical testing.

[0049] Example 7 Preparation of Aqueous Zinc Ion Battery

[0050] 1) Preparation of positive electrode: The aluminum-iron prepared in Example 2 was co-doped with V6O 13 After the electrode material is evenly mixed with PVDF and Super-p, a small amount of NMP is added as a solvent. After being evenly mixed, it is directly applied on the substrate carbon paper, dried in a vacuum drying oven, and taken out to obtain a coating with aluminum-iron co-doped V6O 13 The positive electrode;

[0051] 2) The positive electrode sheet prepared in step 1) was used as the positive electrode, the negative electrode sheet prepared in Example 4 was used as the negative electrode, and 3M zinc trifluoromethanesulfonate was selected as the electrolyte to obtain an aqueous zinc ion battery and perform electrochemical testing.

[0052] Example 8 Preparation of Aqueous Zinc Ion Battery

[0053] 1) Preparation of positive electrode: The aluminum-iron prepared in Example 3 was co-doped with V6O 13 After the electrode material is evenly mixed with PVDF and Super-p, a small amount of NMP is added as a solvent. After being evenly mixed, it is directly applied on the substrate carbon paper, dried in a vacuum drying oven, and taken out to obtain a coating with aluminum-iron co-doped V6O 13 The positive electrode;

[0054] 2) The positive electrode sheet prepared in step 1) was used as the positive electrode, the negative electrode sheet prepared in Example 4 was used as the negative electrode, and 3M zinc trifluoromethanesulfonate was selected as the electrolyte to obtain an aqueous zinc ion battery and perform electrochemical testing.

[0055] Example 9 Preparation of Aqueous Zinc Ion Battery

[0056] 1) Preparation of positive electrode: The aluminum-iron prepared in Example 1 was co-doped with V6O 13After the electrode material is evenly mixed with PVDF and Super-p, a small amount of NMP is added as a solvent. After being evenly mixed, it is directly applied on the substrate carbon paper, dried in a vacuum drying oven, and taken out to obtain a coating with aluminum-iron co-doped V6O 13 The positive electrode;

[0057] 2) The positive electrode sheet prepared in step 1) was used as the positive electrode, the negative electrode sheet prepared in Example 5 was used as the negative electrode, and 3M zinc trifluoromethanesulfonate was selected as the electrolyte to obtain an aqueous zinc ion battery and perform electrochemical testing.

[0058] Example 10 Preparation of aqueous zinc ion battery

[0059] 1) Preparation of positive electrode: The aluminum-iron prepared in Example 2 was co-doped with V6O 13 After the electrode material is evenly mixed with PVDF and Super-p, a small amount of NMP is added as a solvent. After being evenly mixed, it is directly applied on the substrate carbon paper, dried in a vacuum drying oven, and taken out to obtain a coating with aluminum-iron co-doped V6O 13 The positive electrode;

[0060] 2) The positive electrode sheet prepared in step 1) was used as the positive electrode, the negative electrode sheet prepared in Example 5 was used as the negative electrode, and 3M zinc trifluoromethanesulfonate was selected as the electrolyte to obtain an aqueous zinc ion battery and perform electrochemical testing.

[0061] Example 11 Preparation of aqueous zinc ion battery

[0062] 1) Preparation of positive electrode: The aluminum-iron prepared in Example 3 was co-doped with V6O 13 After the electrode material is evenly mixed with PVDF and Super-p, a small amount of NMP is added as a solvent. After being evenly mixed, it is directly applied on the substrate carbon paper, dried in a vacuum drying oven, and taken out to obtain a coating with aluminum-iron co-doped V6O 13 The positive electrode;

[0063] 2) The positive electrode sheet prepared in step 1) was used as the positive electrode, the negative electrode sheet prepared in Example 5 was used as the negative electrode, and 3M zinc trifluoromethanesulfonate was selected as the electrolyte to obtain an aqueous zinc ion battery and perform electrochemical testing.

[0064] According to the six aqueous zinc ion batteries assembled in Examples 6 to 11 above, we obtained that Example 6 had the best electrochemical performance, and the specific capacity was improved at each current density (such as Figure 4 As shown in Example 6, the Al / Fe-V6O formed when the molar ratio of vanadium pentoxide:aluminum nitrate:iron nitrate is 2.2:0.11:0.1 13 It provides more active sites, making it easier to store more zinc ions, while promoting the embedding and extraction of zinc ions, thereby improving its electrochemical performance.

Claims

1. A kind of aluminum-iron co-doped V6O 13 An electrode material, characterized in that The preparation method thereof comprises the following steps: Vanadium pentoxide, aluminum nitrate and ferric nitrate were weighed and dissolved in deionized water and anhydrous ethanol, mixed and stirred at room temperature to fully mix, and the fully mixed solution was transferred to a stainless steel hydrothermal reactor lined with polytetrafluoroethylene for hydrothermal reaction, cooled to room temperature, centrifuged to remove residual reactants, freeze-dried, and then the product was placed in a tubular furnace under a nitrogen environment for calcination to obtain Al / Fe-V6O 13 Electrode material.

2. A kind of aluminum-iron co-doped V6O according to claim 1 13 An electrode material, characterized in that In molar ratio, vanadium pentoxide:aluminum nitrate:iron nitrate = 2.2:0.08~0.13:0.07~0.

12.

3. Aluminum-iron co-doped V6O according to claim 1 13 An electrode material, characterized in that The aluminum nitrate and the iron nitrate are Al(NO3)3·9H2O and Fe(NO3)3·9H2O respectively.

4. A kind of aluminum-iron co-doped V6O according to claim 1 13 An electrode material, characterized in that The hydrothermal reaction conditions are: reaction at 160° C. for 24 hours.

5. The aluminum-iron co-doped V6O according to claim 1 13 An electrode material, characterized in that The calcination condition is calcination at 350° C. for 1 h.

6. Aluminum-iron co-doped V6O according to any one of claims 1 to 5 13 Application of electrode materials in aqueous zinc-ion batteries.

7. The use according to claim 6, characterized in that: The method comprises the following steps: 1) Preparation of positive electrode: Co-doping aluminum and iron with V6O 13 After the electrode material is evenly mixed with the binder and the conductive material, a small amount of NMP is added as a solvent. After being evenly mixed, the mixture is directly applied on the substrate carbon paper, dried in a vacuum drying oven, and taken out to obtain a V6O coated with aluminum and iron co-doped 13 The positive electrode; 2) Preparation of negative electrode: Grind the zinc sheet with sandpaper to remove the oxide layer on the surface, and cut the polished zinc sheet into a circular negative electrode sheet with a diameter of 12 mm; 3) The positive electrode sheet prepared in step 1) is used as the positive electrode, the negative electrode sheet prepared in step 2) is used as the negative electrode, and the electrolyte is 3M zinc trifluoromethanesulfonate to obtain an aqueous zinc ion battery.

8. The use according to claim 7, characterized in that: In step 1), the binder is PVDF.

9. The use according to claim 7, characterized in that: In step 1), the conductive material is Super-p.

10. The use according to claim 7, characterized in that: In step 2), the zinc sheet has a thickness of 0.1 mm to 0.2 mm and a purity of 99% to 99.99%.

Citation Information

Patent Citations

  • Transition metal doped V6O13 nanobelt material as well as preparation method and application thereof

    CN113929140A

  • Preparation method and application of vanadium tridecanoate electrode material for aqueous zinc ion battery

    CN114628680A

  • Vanadium-based aqueous zinc ion battery

    CN118589062A

  • Novel process for the synthesis of vanadium oxide, V6O13

    US4619822A